(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Postoperative hypocalcemia is the most frequent and common complication after total thyroidectomy. It is necessary to diagnose hypocalcemia immediately after total thyroidectomy for minimizing complications. The objective of this study was to measure and to evaluate the serum calcium level in total thyroidectomy patients. This prospective observational study was carried out in the Department of Clinical Pathology in collaboration with Department of Surgery & Department of Otolaryngology of BSMMU and Department of Otolaryngology of DMCH, Dhaka, during the period of September 2010 to August 2011. Total 65 patients were enrolled those came for total thyroidectomy irrespective of age and sex. Hypocalcemia was found in 25 cases and normocalcemia was found in 40 cases. Male were 16.0% and female were 84.0%. Females were predominant. The incidence of hypocalcemia was 38.5%. Asymptomatic hypocalcemia was found in 22 and symptomatic hypocalcemia was found in 3 cases. Hypocalcemia was developed mostly in malignant thyroid diseases. The mean difference of intraoperative (20 minutes after total thyroidectomy), after 24 hours and after 48 hours calcium levels were statistically significant (p<0.05) between patient with hypocalcemia and patient with normocalcemia in unpaired t-test. Serum calcium level significantly decreased after total thyroidectomy and most critical time is first 24 hours of post-thyroidectomy period. If clinical sign symptoms of hypocalcemia are not developed in this period, patient is safe and can be discharged from hospital. DOI: http://dx.doi.org/10.3329/bjmb.v4i1.13775 Bangladesh J Med Biochem 2011; 4(1): 4-9